IMPLEMENTATION AND SYSTEMATIZATION OF A COMPREHENSIVE MEDICATION MANAGEMENT (CMM) SERVICE DELIVERED TO WOMEN WITH BREAST CANCER - Ribeiro, Maria Angela; MENDONÇA, SIMONE DE ARAÚJO MEDINA; Ribeiro Filardi, Agnes Fonseca; Dos Anjos, Anna Claudia Yokoyama; RAMALHO-DE-OLIVEIRA, DJENANE (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The aim of the present study was to describe the process of implementation and systematization of a comprehensive medication management (CMM) service, from the perspective of the participants involved, in a high complexity service that cares for women with breast cancer in Brazil. Methods: A qualitative study that utilized action research that followed the procedures proposed by Kurt Lewin and the ethical and clinical principles of pharmaceutical care practice. Data collection techniques were participant observation between August 2014 and December 2016, semi-structured interviews with eight pharmacists and pharmacy residents, field notes, and analysis of documents. Results: Six major themes emerged in four cycles of the action research process: (1) Resistance is human; the management of conflict is necessary; (2) insecurity with being a clinician; (3) management of change supported by driving forces; (4) pharmaceutical care fostering professionals' self-efficacy; (5) documentation as the conducting wire of the practice; and (6) the advantages of a systematized practice. Conclusion: The study offered an understanding of the process of implementation of CMM services from the perspective of pharmacists. It produced knowledge on the experiences of pharmacists as they lived through the process of transformation of their professional practice to offer a patient-centered and systematized service. The framework of Lewin supported the introduction of a new work path for pharmacists, which could be operationalized as an innovative technology for the Brazilian health-care system: CMM services.